Rapid Identification of Chemical Constituents in Erigeron breviscapus Injection Based on UHPLC-LTQ-Orbitrap MSn and Molecular Network Technology - ZHANG Yu-ting;WANG Chun-guo;DENG Xin-qi;YAN Xing-li;LIU Yao-yu;LAN Yu;WANG Yu-hang;WANG Jia-ping;JIN Zhong-xian;SHI Jin-li;ZHANG Shuo-feng (Zhipu Xuebao, 2023)
Erigeron breviscapus injection is widely used in clinical treatment of ischemic stroke and coronary heart disease. More than 80 chemical components have been identified from Erigeron breviscapus herb. However, chemical components of Erigeron breviscapus injection remain unclear. In this study, a rapid qualitative method of ultra-performance liquid chromatography-linear ion trap/electrostatic field Orbitrap combined high resolution mass spectrometry (UHPLC-LTQ-Orbitrap MS) coupled with molecular network was established for identification of Erigeron breviscapus injection. UPLC BEH C18 column (2.1 mm×50 mm×1.7 μm) was employed and the gradient elution was carried out with the mobile phase of acetonitrile-0.1% formic acid aqueous solution. According to the similarity of MS/MS fragmentation patterns, GNPS molecular network was established based on LTQ-Orbitrap MS data, which was collected in positive and negative ion modes, respectively. Molecules with similar structure were screened and clustered with Cytoscape 3.6.1 software. Components in Erigeron breviscapus injection were further identified based on information of retention time, molecular weight, and MSn multistage fragmentations. The result of GNPS molecular network displayed two major component communities of caffeinyl ester derivatives and flavonoids. Component community of caffeinyl ester derivatives was established based on seed nodes of chlorogenic acid, isochlorogenic acid, and erigoster B. Component community of flavonoids was established based on seed nodes of scutellarein and scutellarin. Eighty-four components, including mono-caffeoyl esters, di-caffeoyl esters, tri-caffeoyl esters and flavonoids, were identified in the major component communities of Erigeron breviscapus injection, of which 49 were identified in Erigeron breviscapus injection production for the first time. This study provides reference for quality control and pharmacodynamics research of Erigeron breviscapus injection.